ROLE OF EXTENDER ADDITIVES AND AI TECHNICIANS IN IMPROVING FIRST SERVICE CONCEPTION RATE WITH FROZEN SEMEN IN CATTLE AND BUFFALOES UNDER FIELD CONDITIONS - DHAMI, A J; CHATURVEDI, DEVANGANA; THESIA, M J; CHAUDHARI, D V; PATEL, B S (The Indian Journal of Animal Reproduction, 2023)
This study involved semen ejaculates with >75 % initial motility of 3 Gir and 3 Murrah bulls split-diluted at 100million sperm per ml using Tris-citric acid-fructose-egg yolk-glycerol (TFYG) extender without (control) and withfortification of additives Mifepristone (10 μg/ml), Sericin (5 mg/ml) and Taurine (4 mg/ml) and frozen in French ministraws using a programmable biofreezer. The straws were thawed in water bath at 37°C for 30 sec. The frozen semendoses of buffalo (1446) and cattle (495) so prepared were distributed among 18 good to average performing AItechnicians of Panchamahals District Cooperative Milk Producers Union Limited, Godhara (Gujarat). Irrespective ofadditives, the overall first AI conception rate, and the mean post-thaw percent sperm progressive motility, viability,HOS reactivity, CTC assay (non-capacitated sperm, ‘F’ pattern) and CASA traits, viz., VAP (μm/s), VCL (μm/s), (VSL(μm/s) and ALH (μm) recorded in Gir bull semen were 47.07, 46.73±0.67, 63.99±0.83, 54.36±0.78, 65.56±0.95,30.89±0.63, 73.68±1.03, 23.98±0.65 and 1.86±0.04, respectively. The corresponding figures for Murrah bull semenwere 50.76, 48.81±0.82, 65.63±0.70, 56.64±0.64, 68.80±0.82, 33.35±0.72, 72.26±0.83, 27.29±0.83 and 1.90±0.04.All values where apparently or statistically better in Murrah than Gir bull semen. The effect of extender-additives washighly significant (p
Keywords: AI technicians; Bovine semen; Cryocapacitation; Extender additives (Mifepristone, Sericin & Taurine); invivo fertility; Post-thaw sperm quality